Housing crisis and urban inequality in Latin America - Godoy, Jeane Aparecida Rombi de; Benini, Sandra Medina; Gulinelli, Erica Lemos (National Journal of City Management, 2025)
Objective – To critically analyze the housing crisis in Latin America as a structural expression of social and urban inequality, demonstrating how housing, rather than promoting inclusion, has operated as a mechanism of exclusion and reproduction of socio-spatial hierarchies. Methodology – The study adopts a qualitative, critical-interpretative approach, based on a literature review and documentary analysis of multilateral organizations, combined with a comparative case study strategy (Brazil, Mexico, and Colombia), mobilizing categories such as coloniality, the right to the city, uneven urbanization, financialization, and intersectionality. Originality/relevance – The article contributes to critical debate by shifting the understanding of the housing crisis from a technical-quantitative perspective to a structural interpretation, highlighting its links to coloniality, financialization, and the reproduction of urban inequalities. It articulates critical social theory with comparative empirical evidence in Latin America, revealing gaps in traditional approaches to housing policies. Results – The analysis identifies common patterns across the region, such as peripheralization, the capture of housing policies by market interests, and the production of precarious solutions, as well as national specificities: in Brazil, the production of new peripheries; in Mexico, the mass abandonment of housing units; and in Colombia, precariousness associated with forced displacement. It concludes that social housing has reproduced rather than mitigated inequalities. Theoretical/methodological contributions – The study proposes understanding housing as a central analytical category in the production of urban inequalities, integrating different theoretical frameworks (coloniality, financialization, uneven urbanization, and intersectionality), and demonstrating the analytical strength of comparative approaches in revealing structural patterns in Latin America. Social and environmental contributions – The study highlights the need to reorient housing policies toward the promotion of the right to the city, advocating land regulation, the capture of land value increments, the production of well-located housing, and the incorporation of racial, gender, and environmental equity perspectives, aiming to reduce socio-spatial segregation and improve living conditions.